Impact of Physiotherapy on Physical Capacity of 7–11-Year-Old Children with Autism Disorder (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2014)
Research background. Autism is one of the most difficult wide spectrum developmental disorders. Recently, striking increase in the number of autistic children is observed. Physical activation is important for the development and physical fitness of children with autism disorder. Research object – children’s balance, muscle strength and endurance. The aim was to evaluate physical capacity and impact of physiotherapy on balance, muscle strength and endurance in 7–11-yearold children with autism disorder. Methods. The study group consisted of 10 children with autism disorder (8 boys and 2 girls), the control group consisted of 18 healthy children (15 boys and 3 girls). The average age of the study group was 8.90 ± 1.4 years; in the control group 8.94 ± 1.0 years. Balance of children was assessed by Berg Balance Scale, hand grip – by dynamometry, leg muscle strength – by long jump test and squat test, and endurance of abdominal muscle – by sit up test. The results showed that physical condition of children with autism disorder was significantly poorer compared to healthy children: the balance – 43.9 ± 7.82 v. s. 55.4 ± 0.9 points; right hand muscle strength of 5.9 ± 2.06 kg v. s. 12.2 ± 3.43 kg; left – 5.3 ± 1.87 kg v. s 12.1 ± 3.43; long jump 43.0 ± 25.25 cm v. s 132.6 ± 31.87 cm; endurance of abdominal muscles 7.3 ± 2.01 v. s 19.6 ± 4.06 times per 30 s; squats 9.1 ± 4.36 v. s 27.6 ± 7.07 times per 30 s. After applying physical therapy results of all performed tests in children with autism improved significantly: balance to 49.9 ± by 5.45 points, right hand muscle strength to 7.9 ± 2.49 kg, left – 7.5 ± 2.31 kg, long jump to 79.2 ± 39.87 cm, crunches to 11.8 ± 4.54 times, squats to 14.8 ± 4.83 times, but they did not reach the results of healthy children. Conclusion. Balance, muscle strength and endurance of children with autism disorder were significantly lower than those in healthy children. Physical therapy significantly improved physical capacity of autistic children, but the level of healthy children was not reached.Keywords: autism, children, physiotherapy.